2022
DOI: 10.1080/09670874.2022.2058709
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic nematodes for control of potato tuber moth (Phthorimaea operculella [Zeller], (Lepidoptera: Gelechiidae) in infested tubers

Abstract: The potato tuber moth PTM, Phthorimaea operculella, is one of the most economically important potato pests worldwide. In the present study, the potential of Steinernema feltiae and Steinernema carpocapsae for controlling PTM in potato tubers was evaluated compared to alpha-cypermethrin. Steinernema carpocapsae in both concentrations (12.6×10 6 IJs and 6.2×10 6 IJs) showed a lower number of emerged insects than alpha-cypermethrin (10 mg ai l -1 ).Alpha-cypermethrin (20 mg ai l -1 ) showed the highest efficacy a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…According to Wilson et al [ 91 ], due to the adaptation to habitats other than mineral soils, such as peat, leaf litter, or wood, it is also capable of cruising long distances toward hosts, behaving as both an ambusher and a cruiser in such environments. The cruising behavior of S. carpocapsae has also been recently confirmed by Ebrahimi et al [ 92 ], who studied the efficacy of S. carpocapsae on Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae). Additionally, Baiocchi et al [ 93 ] observed that the host-seeking behavior of S. carpocapsae was enhanced when stimulated with the physical contact of the host cuticle.…”
Section: Discussionmentioning
confidence: 59%
“…According to Wilson et al [ 91 ], due to the adaptation to habitats other than mineral soils, such as peat, leaf litter, or wood, it is also capable of cruising long distances toward hosts, behaving as both an ambusher and a cruiser in such environments. The cruising behavior of S. carpocapsae has also been recently confirmed by Ebrahimi et al [ 92 ], who studied the efficacy of S. carpocapsae on Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae). Additionally, Baiocchi et al [ 93 ] observed that the host-seeking behavior of S. carpocapsae was enhanced when stimulated with the physical contact of the host cuticle.…”
Section: Discussionmentioning
confidence: 59%